Os movimentos dos planetas e os modelos de universo : uma proposta de sequência didática para o ensino médio - Barros, Marconi Frank (2014)
The research aimed to develop a instrucional sequence on relevant topics of Astronomy and check if the used methodology and materials were appropriated and have brought about a meaningful learning in a group of 33 students of the third year of secondary education at a public school of Espirito Santo state, Brazil, with whom the sequence was worked. The main theoretical framework used in the preparation of the sequence and assessment of their results has been the Theory of Meaningful Learning of David Ausubel and Joseph Novak. The sequence had as general theme "The Planets Movements and the Models of Universe", whose education to students was based on the preparation of a potentially significant material and activities involving observation of the sky with the naked eye and telescope, complemented with the use of the Stellarium astronomical software; a historical approach of the theme in the classroom, since the beginnings of Astronomy up to the current times, with an emphasis on the transition from the geocentric universe model to an heliocentric one; a planetarium session and a practical activity of simulation of planetary movements using the student’s body itself. A substantial part of the activities were worked out after the application and analysis of two initial questionnaires and the elaboration by the students of conceptual maps to check their prior knowledge on the subject. This survey helped to guide the intervention. For collecting data, monitoring and assess the learning brought about by the sequence, another questionnaires were applied and new conceptual maps were developed by the students after the completion of the sequence. It was also possible to interact and stimulate students through distance by means of a group page on Astronomy created at the Facebook social network. The analysis of the collected data permit to detect evidences of a significant learning in a substantial part of the students who have demonstrated interest in the subject and have been able to assimilate new concepts about the sky and the planets, to reconcile concepts initially considered as distinct, as the sky and Universe, and understand the explanations about the planets movements in accordance with the geocentric and heliocentric models, simulated in the activity of representation of these movements with the body itself. The comparison between the conceptual maps drawn up before and after the sequence also showed evidence of advances that have occurred in the learning of concepts of Astronomy. A growing of interest in the discipline of Physics was also detectec. However, the data also showed that not all of the students learned significantly, indicating some points in which the material and the methodology used still deserve to be reviewed and improved in future applications, such as in the case of the teaching of the retrograde movement concept. As a product associated with the dissertation, all potentially significant material used, the scripts and examples of practical activities applied and the instructional sequence structuring were gathered and are presented at the end, in the form of a didactic teaching proposal for topics of Astronomy in high school, that follows as an appendix to this dissertation.